Optimization of Tenjolaya Tourism Village Marketing Strategy Through Digital Technology and Social Media Utilization - Nurvita Trianasari; Deannes Isynuwardhana; Ruri Octari Dinata; Aulia Ferina Sendhitasari (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Tenjolaya Village, situated in the Ciwidey Region, Rancabali, Bandung Regency, possesses significant potential as a tourism village due to its natural beauty and distinctive products such as orange kalua. However, the management and marketing of this tourism village still face challenges, including the ineffective utilization of digital technology and social media. This community service activity aims to enhance the village's marketing strategy through training and assistance in digital technology and social media utilization. Involving local communities, the training covered materials on digital content management, social media-based marketing, and activity outcome evaluation. The training results demonstrated a significant improvement in participants' understanding and capabilities, as evidenced by an increase in the average score from 83.18 before training to 93.64 after training (p<0.05). This activity provides hope that Tenjolaya Village can gain more recognition and attract more visitors, thereby impacting the village's economic growth.